Pemaknaan Aset Waqaf dan Bentuk Pelaporanya di Pondok Pesantren Daruttaqwa Gresik - Nur Syamsiyah; Ari Kamayanti; Yusna Yusna (JIATAX (Journal of Islamic Accounting and Tax), 2019)
The purpose of this study is to know the Waqaf Asset Treatment and the form of Reporting at Daruttaqwa Gresik Islamic Boarding School. This is a descriptive research. The data used are primary data in the form of interviews with caregivers (Nyai), Deputy Head of Pondok, Treasurer, Hodam and Santri. Secondary data are in the forms of documentation. The results of the study show that the value of the waqaf’s perception as an Islamic boarding school asset is based on a will, blessing, reverence and sincerity. While Islamic boarding schools does not reflect the reporting in accounting rules by IAI (not the detail), but rather based on trust. On the other hand, Islamic boarding school accounting guidelines does not cover all the waqaf assets, which cause a discrepancy between the reality found in the pesantren and the pesantren accounting guidelines. The conclusion of this study is that the regulation of IAI have not been able to cover most of aspects in pesantren so that the pesantren value can’t be implemented in reporting their accounting report. It is suggested that IAI can help evaluate pesantren accounting guidelines so that the pesantren values can be implemented in reporting.